Determinants of sustainability among beach resorts / Ma. Joy G. Soriano - G. Soriano, Ma. Joy (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2022)
The overwhelming influx of tourists in the beautiful and pristine beaches has brought enormous contribution to both economic and social development of local communities, however, it does not come without any cost to the environment. As such, beach resort owners were confronted with pressing issues relating to sustainability design and implementation. Hence, this study was initiated to understand the determinants of the sustainability of beach resorts in Davao Region as well as provide an implication on the sustainability framework for local policy development. A mixed methods research design utilizing convergent parallel approach was employed in which a total of 215 beach resort owners participated in this study. Results of the quantitative portion revealed that corporate social responsibility and tourism promotion services are the significant determinants of sustainable tourism in Davao Region and the qualitative insights of the beach resort owners revealed the there is a necessity to promote the tourism activities, products, and services; trainings and orientation needs to be initiated, and CSR awareness may be promoted and strengthened. As to the corroboration of the quantitative and qualitative findings, merging confirmation was noted for all of the constructs denoting a parallel results of both qualitative and quantitative strands of the study.